Comparative transcriptomic analysis and validation of the ovary and testis in the ridgetail white prawn (Exopalaemon carinicauda) - Jia, Shaoting; Jin, Ling; Lv, Jianjian; Wang, Jiajia; Li, Jitao; Liu, Ping; Li, Jian (Frontiers in Marine Science, 2022)
The ridgetail white prawn, Exopalaemon carinicauda is an important cultured seawater species in China. As female E.carinicauda grows faster than males, it is significant to search for the differentially expressed genes (DEGs) between males and females. However, there is no public available E.carinicauda genome data, and genes related to E. carinicauda sex differences are unclear. In this study, the transcriptome sequencing for ovary and testis tissues of E. carinicauda were conducted, and 20,891 DEGs were identified including 11,709 up-regulated DEGs and 9,182 downregulated DEGs. The functional categories related to meiosis and reproduction were enriched as well as the steroidogenesis KEGG pathway was clustered. Furthermore, the genes related to male reproduction and cell cycle were dug out which were verified by real-time PCR. In addition, two-color fluorescence in-situ hybridization result showed that foxj1b might play roles in ovary development during early stage. Therefore, our study provides clues for the study of reproductive-related gene function in E.carinicauda.